Taxonomic insights into the phylogeny of Bacillus badius and proposal for its reclassification to the genus Pseudobacillus as Pseudobacillus badius comb. nov. and reclassification of Bacillus wudalianchiensis Liu et al. - Verma, Ashish; Pal, Yash; Ojha, Anup Kumar; Kumari, Munesh; Khatri, Indu; Rameshkumar, N.; Schumann, Peter; Dastager, Syed G.; Mayilraj, Shanmugam; Subramanian, Srikrishna; Krishnamurthi, Srinivasan (Systematic and Applied Microbiology, 2019)
The species Bacillus badius is one of the oldest members of the genus Bacillus isolated from faeces of children and was classified based on its ability to form endospores [8]. In 16S rRNA gene sequence and phylogenetic analysis, Bacillus badius DSM 23(T) shared low similarity (93.0%) and distant relationship with B. subtilis, the type species of the genus Bacillus indicating that it does not belong to this genus. Additional strains of the species, B. badius DSM 5610, DSM 30822 and B. encimensis SGD-V-25 (which has been recently reclassified as a member of this species) were included in the study to consider intraspecies diversity. Detailed molecular phylogenetic and comparative genome analysis clearly showed that the strains of B. badius were consistently retrieved outside the cluster of Bacillus sensu stricto and also distantly related to the genera Domibacillus and Quasibacillus. Further, the data from biochemical reactions (inability to ferment most carbohydrates), polar lipids profile (presence of diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine and an aminophosphoglycolipid) and fatty acids supported the molecular analysis. Thus the four B. badius strains; DSM 23(T), DSM 5610, DSM 30822 and SGD-V-25 displayed sufficient demarcating phenotypic characteristics that warrant their classification as members of a novel genus and single species, for which the name Pseudobacillus badius gen. nov. comb. nov. is proposed with Pseudobacillus badius DSM 23(T) (= ATCC 14574(T)) as the type strain. Additionally, based on our findings from phenotypic, chemotaxonomic and genotypic parameters, Bacillus wudalianchiensis DSM 100757(T) was reclassified as Pseudobacillus wudalianchiensis comb. nov. (C) 2019 Elsevier GmbH. All rights reserved.
Keywords: 16S rRNA; Bacillus; Bacillus wudalianchiensis; Fatty acids; polar lipids; Pseudobacillus

Total synthesis of (-)-2-methoxy-2-butenolide-3-cinnamate and its antimicrobial potentials - Said, Madhukar S.; Udavant, Rohini; Sahu, Amit Kumar; Khan, Abujunaid; Nayak, Rashmi; Dastager, Syed G.; Kumar, Pradeep; Gajbhiye, Jayant (Natural Product Research, 2020)
The first total synthesis of (-)-2-methoxy-2-butenolide-3-cinnamate (butenolide cinnamate) was achieved using commercially available starting material. The synthesized compound was found to have promising antibacterial activity against Gram-negative strainsEscherichia coli(ATCC 8739),Salmonella typhimurium(ATCC 23564) andPseudomonas aeruginosa(ATCC 19154) with a minimum inhibitory concentration of 2.0 mu g/mL, 1.0 mu g/mL and 2.0 mu g/mL, respectively. Notably, the compound was more potent against Gram-negative test strains than the Gram-positive test strains.
Keywords: antibacterial activity; butenolide cinnamate; Total synthesis

Transition metal complexes of Thiadiazole-Picolinic acid: Crystal structures, DFT insights and anticancer activity - Torambetov, Batirbay; Khojabaeva, Gulnaz; Bharty, M. K.; Gupta, Sushil K.; Kadirova, Shakhnoza; Pradeep, S.; Dastager, Syed G.; Gonnade, Rajesh G. (Journal of Molecular Structure, 2026)
Five novel transition metal complexes [Ni(H2aeth)2(Pic)2] (1), [Co(H2aeth)2(Pic)2] (2), [Ni(H2aeth)2(Pic)(HPic)] ClO4 (3), [Co(H2aeth)2(Pic)(HPic)]ClO4 (4) and [Zn(H2aeth)2 (Pic)(HPic)]ClO4 (5) were synthesized using a 2amino-5-ethylthio-1,3,4-thiadiazole (H2aeth) and picolinic acid (HPic) as co-ligands. These complexes were characterized by FT-IR, UV-Vis., X-ray photoelectron spectroscopy, TG-DTA, and single-crystal X-ray techniques. Crystallographic analysis confirmed distorted octahedral geometries around the metal centers with extensive hydrogen bonding networks promoting supramolecular assembly in the solid state. X-ray photoelectron spectroscopy (XPS), validated the +2 oxidation state of each metal center. Thermal studies indicated multistep decomposition processes resulting in the formation of metal oxides. Density functional theory (DFT) and timedependent DFT calculations were employed to explore electronic structures and predict UV-Vis. transitions, which showed good agreement with experimental data. Frontier molecular orbital (FMO) analysis revealed that Ni(II) complexes 1 and 3 are softer and more reactive, consistent with their observed biological activity. The anticancer potential of complexes 1-5 was evaluated in vitro using the MCF-7 human breast cancer cell line and the MTT assay. Complex 1 exhibited the strongest cytotoxicity (IC50 = 26.5 mu g/mL) followed by complexes 3 (34.9 mu g/mL), 4 (46.4 mu g/mL), 2 (81.1 mu g/mL), and 5 (103.3 mu g/mL). The observed activity trends correlate with metal identity and coordination environment, underlining the role of electronic and structural factors in modulating bioactivity. These findings suggest that thiadiazole-picolinate metal complexes, particularly those based on Ni (II), are promising scaffolds for anticancer drug development.
Keywords: Anti-cancer activity; crystal structure; DFT calculation; MCF-7 cell line; Picolinic acid; Thiadiazole complexes